2019
DOI: 10.1177/0272684x19874967
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Information-Seeking Behaviors on Dietary Supplements

Abstract: Background Consumers are advised to seek information about dietary supplements (DS) before using them; little is known concerning whether this recommendation is heeded. Objective The objectives of this pilot study were to investigate whether users of DS seek information about these products before using them and particularly whether such information is sought from health-care professionals (HCPs). Methods Surveys administered face-to-face to adult consumers at three venues in New York City. Results Between Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the existing literature, it is reported that people, including PwMS who use DIHES, often receive their information on DIHES from sources such as family, friends, books, magazines, or the internet [6,[36][37][38]. The present study finds that from the participants' perspective, knowledge regarding DIHES did not have to be scientifically based to be perceived as valid and useful.…”
Section: What Constitutes Useful Knowledge?mentioning
confidence: 58%
“…In the existing literature, it is reported that people, including PwMS who use DIHES, often receive their information on DIHES from sources such as family, friends, books, magazines, or the internet [6,[36][37][38]. The present study finds that from the participants' perspective, knowledge regarding DIHES did not have to be scientifically based to be perceived as valid and useful.…”
Section: What Constitutes Useful Knowledge?mentioning
confidence: 58%
“…The survey instrument was developed based on an extensive literature review. Research articles discussing the reasons for consultation with pharmacists around HDS use [ 40 , 41 , 44 , 45 , 46 , 47 ], pharmacist- or HCP-patient communication and relationship [ 48 , 49 ], and complementary medicine disclosure to HCPs [ 50 , 51 , 52 ] were used. Based on the literature review, the consultation and non-consultation with CPs about HDSs can be influenced by the consumers’ perceptions of the consultative roles of CPs with respect to HDSs, facilitators (e.g., having a good relationship with CPs, having adequate time to consult CPs, willingness of CPs to spend time providing consultation, etc.…”
Section: Methodsmentioning
confidence: 99%
“…9 A complex interplay of an aging population, interest in integrative medicine, and distrust of prescription drugs contributes to this upsurge in dietary supplement use. 10 As a result, student pharmacists should receive adequate education on dietary supplements, and be able to assess their appropriateness for specific individuals who may have comorbid conditions and concomitant drugs. Opportunities to practice communication and patient counseling skills in a safe, nonjudgmental environment is essential.…”
Section: Introductionmentioning
confidence: 99%
“…9 A complex interplay of an aging population, interest in integrative medicine, and distrust of prescription drugs contributes to this upsurge in dietary supplement use. 10…”
Section: Introductionmentioning
confidence: 99%